1987
DOI: 10.1080/03014468700009351
|View full text |Cite
|
Sign up to set email alerts
|

Finger ridge count in Basque populations: univariate and multivariate comparison with other Spanish populations

Abstract: We have analysed finger ridge counts in the indigenous Spanish Basque population (841 males and 911 females). Bimanual and sexual variation have proved to be statistically significant. The results in the Basque population were compared with those of other Spanish populations. In the univariate comparison statistically significant differences appear. The means found in the Basque population are the lowest. Our population is situated on the lower part of the variation range of the European populations for whom d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Thus, even when the areas analysed for thumbprint ridge density in our study differ from that of the earlier studies, [2][3][4][5][6][12][13][14][15][16][17][18][22][23][24][25][26][27][28] the basic quantitative differences remain the same, i.e., females have a higher finger (thumb) print ridge density than males which is in accordance with earlier studies on different ethnic groups. 2,[5][6][7][8][13][14][15][16][17][18][22][23][24][25][26][27][28] Ridge thickness and furrows are the two important factors which determine the density of ridges. Cummins et al, 24 Ohler et al, 25 Kralik et al 26 and Moore 28 worked on the ridge thickness in fingerprints and showed that males have coarser finger ridges than females which suggests that males will have less ridges in a given area than females and thus a lower ridge density.…”
Section: Roc Locsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, even when the areas analysed for thumbprint ridge density in our study differ from that of the earlier studies, [2][3][4][5][6][12][13][14][15][16][17][18][22][23][24][25][26][27][28] the basic quantitative differences remain the same, i.e., females have a higher finger (thumb) print ridge density than males which is in accordance with earlier studies on different ethnic groups. 2,[5][6][7][8][13][14][15][16][17][18][22][23][24][25][26][27][28] Ridge thickness and furrows are the two important factors which determine the density of ridges. Cummins et al, 24 Ohler et al, 25 Kralik et al 26 and Moore 28 worked on the ridge thickness in fingerprints and showed that males have coarser finger ridges than females which suggests that males will have less ridges in a given area than females and thus a lower ridge density.…”
Section: Roc Locsupporting
confidence: 92%
“…1 Amongst the number of parameters available for establishing the identity of an individual, fingerprints are considered to be the most precise and reliable indicators of personal and gender identification. [2][3][4][5][6][7][8] No two fingers are found to have identical prints, and it is an overwhelming mathematical probability that no two will ever be found to match. 9 It has been estimated that chances of two persons having identical finger impressions are about one in sixty-four thousand million of the world population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies comparing male and female FA scores have produced mixed results (e.g. Micle & Kobyliansky 1988;Bogle 1989;Thornhill & Gangested 1994;Arrieta et al 1995;Manning 1995;Wilson & Manning 1996;Yeo et al 1997;Trivers et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Among the number of parameters available for establishing the identity of an individual, fingerprints are extensively used in providing a clue regarding identity. [1][2][3][4][5][6][7] No two fingers are found to have identical prints, and it is an overwhelming mathematical probability that no two ever will be found to match. 8 The ridge patterns are formed in the human fetus before birth and remain the same throughout a person's life and even after death until they are lost through decomposition.…”
Section: Introductionmentioning
confidence: 99%